Acaricidal activity of synthetic spilanthol derivative against ticks of medical and veterinary importance - Anholeto, Luis Adriano; Brancaglion, Guilherme Andrade; Santos, Danilo Martins dos; Kapritchkoff, Rafaela Tami Ikeda [UNESP]; Castro, Karina Neoob de Carvalho; Canuto, Kirley Marques; Rodrigues, Rodney Alexandre Ferreira; Correa, Daniel Souza; Chagas, Ana Carolina de Souza; Pastre, Julio Cezar (Elsevier, 2024)
The ANESPSAT, a synthetic spilanthol derivative, and its nanoformulation were evaluated against Rhipicephalus microplus and Amblyomma sculptum ticks. ANESPSAT activity was compared with spilanthol and derivatives (ANESPE and others). The compound was synthesized in a gram-scale by a 2-step process, comprising a direct ester amidation and a Horner-Wadsworth- Emmons reaction. The nanoemulsions were produced by coarse homogenization followed by high-energy ultrasonication, in which hydrodynamic diameter, polydispersity index, and zeta potential remained stable. The spilanthol-eugenol hybrid derivatives did not show significant acaricidal activity. ANESPE killed 83% of the R. microplus larvae at 30 mg.mL−1, while ANESPSAT killed 97% at 0.5 mg.mL−1, showing to be the most active compound. Spilanthol and ANESPSAT had similar high mortality rates for tick larvae, with LC50 values of 0.10 and 0.14 mg.mL−1 for R. microplus larvae, and 0.04 and 0.48 mg.mL−1 for A. sculptum larvae, respectively. The efficacy of spilanthol was lower against R. microplus engorged females when compared with ANESPSAT, which was highly effective (>98%) against R. microplus engorged females. The nanoemulsion with ANESPSAT was effective against tick females, preventing egg laying and achieving 100% efficacy at 2.5 mg.mL−1. Spilanthol had only 59% efficacy at 10 mg.mL−1. The results suggest that ANESPSAT, a natural product derivative, could be used in novel formulations for tick management that might be safer and environmentally friendly.
Keywords: Acmella oleracea; Bovine parasite sadness; Brazilian Spotted Fever; Cattle tick; Control; Nanoformulation; Rickettsia rickettsii; Spilanthol